TEACHING GRAMMAR EFFECTIVELY USING MOBILE APPS FOR UPPER GRADES - Feruza Erkulova, Feruza Erkulova (Журнал иностранных языков и лингвистики, 2021)
This article discusses how to use apps in teaching English at schools effectively. As we know nowadays learning and teaching Grammar anywhere in the world let alone Uzbekistan has become easy and interesting with the advent of online tools such as computers, mobiles, and social media such as Blog, Twitter, Facebook, Skype, Moodle, etc. Online instruction promotes language learning. During the quarantine period teachers and students are learning to use effectively social media both in teaching and learning process. It is well known that language is guided by Grammar for correct usage so that proper meaning is given to the words and sentences used. Grammar enables learners to use language to describe the world in terms of how, when and where things happen. Keeping this in view, technology is adapted for learning and teaching purposes, to meet the demands of man and enable him to attain the imperishable and flawless treasure of learning. This paper aims at listing and evaluating some of the technological tools used for effective teaching and learning of grammar.